Interpersonal Communication of Foster Guardians in Overcoming Affluenza at Pondok Pesantren Nurul Jadid - Mushariawan, Ilham; Yusuf, Mochamad Aris (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
Affluenza affects not only the general public, but students at Pondok Pesantren Nurul Jadid, Paiton are also affected by affluenza. Simple synonymous students become luxurious lives. Like buying stuffbrandedAccording to some foster parents, many students experience that their intensity is recognized. To overcome this, the advice from the Kyai alone is not enough; intensive guidance and treatment are needed; Foster parents help the Kyai in guiding and educating the santri, and the role of communication is very influential in overcoming affluenza, especially interpersonal communication. Researchers used descriptive qualitative methods; data were analyzed using Harold Granfinkel's ethnomethodology and Ekman Friesen's functionalist structure. The results in this article show that in dealing with student affluenza, foster parents use two models of interpersonal communication: 1). Interpersonal (verbal) communication, foster carers provide understanding and advice regarding the dangers of affluenza and foster carers also try to find out what the reasons are for students suffering from affluenza. 2). Interpersonal communication (Nonverbal) foster carers also use nonverbal communication such as stroking the head, holding the shoulder, smiling, where the meaning of this nonverbal communication is to replace, emphasize and support verbal messages.